Concentrations of viable oil-degrading microorganisms are increased in feces from Calanus finmarchicus feeding in petroleum oil dispersions. Issue 1 (15th September 2015) - Størdal, Ingvild Fladvad; Olsen, Anders Johny; Jenssen, Bjørn Munro; Netzer, Roman; Hansen, Bjørn Henrik; Altin, Dag; Brakstad, Odd Gunnar
Highlights: Zooplankton may contribute to oil fate through ingestion of oil droplets. Feces were collected from Calanus finmarchicus after exposure to oil dispersions. Oil-containing feces had high concentrations of oil-degrading activity. Total bacterial communities were similar between clean and oil-containing feces. Zooplankton feces can contribute to high oil-degrading activity during oil spills. Abstract: Zooplankton are suggested to be biotic contributors to the transport and weathering of oil in marine environments due to their ingestion of oil. In the present experiment, feeding activity and microbial communities in feces from Calanus finmarchicus feeding in oil dispersions were characterized. Feeding activity was significantly reduced in oil dispersions. The microbial communities in clean and oil-containing copepod feces were dominated by Rhodobacteraceae family bacteria ( Lesingera, Phaeobacter, Rugeria, and Sulfitobacter ), which were suggested to be indigenous to copepod feces. The results also indicated that these bacteria were metabolizing oil compounds, as a significant increase in the concentrations of viable oil degrading microorganisms was observed in oil-containing feces. This study shows that bacteria in feces from copepods feeding in dilute oil dispersions have capacity for degradation of oil. Zooplankton may therefore contribute to weathering of oil by excreting feces with microbial communities already adapted to degradation of oil.